Effect of ω-3 Polyunsaturated Fatty Acids-Derived Bioactive Lipids on Metabolic Disorders - Duan, Jinjie; Song, Yayue; Zhang, Xu; Wang, Chunjiong (Frontiers in Physiology, 2021)
Arachidonic acid (ARA) is an important ω-6 polyunsaturated fatty acid (PUFA), and docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and n-3 docosapentaenoic acid (n-3 DPA) are three well-known ω-3 PUFAs. These fatty acids can be metabolized into a number of bioactive lipids. Eicosanoids derived from ARA have drawn great attention because of their important and complex biofunctions. Although EPA, DHA and n-3 DPA have also shown powerful biofunctions, we have fewer studies of metabolites derived from them than those from ARA. Recently, growing research has focused on the bioaction of ω-3 PUFA-derived metabolites, which indicates their great potential for treating metabolic disorders. Most of the functional studies of these bioactive lipids focused on their anti-inflammatory effects. However, several studies elucidated their direct effects on pancreatic β cells, hepatocytes, adipocytes, skeletal muscle cells and endothelial cells. These researches revealed the importance of studying the functions of metabolites derived from ω-3 polyunsaturated fatty acids other than themselves. The current review summarizes research into the effects of ω-3 PUFA-derived oxylipins on metabolic disorders, including diabetes, non-alcoholic fatty liver disease, adipose tissue dysfunction and atherosclerosis.